ISSUES IN TEACHING MEDICAL SCIENCES USING MULTIMEDIA ELECTRONIC TOOLS - Karimoiv Izzatulla Kamoliddin ugli (The Conference Hub, 2025)
The application of multimedia electronic devices in the teaching of medical sciences has transformed learning processes, enhancing students' learning experiences and outcomes. However, the application of these technologies has several challenges, which instructors must manage. This article discusses the most important issues related to the application of multimedia tools in medical education, such as accessibility differences, faculty training needs, information overload risks for students, and the need to preserve pedagogical quality during technology developments. We also discuss ways to address these challenges and identify best practices for maximizing multimedia application in medical curricula. By addressing these issues, schools can also prepare upcoming healthcare professionals in an increasingly digital world.
Keywords: Medical education, multimedia tools, electronic learning, teaching challenges, educational technology, student engagement, accessibility in education, faculty training, pedagogical strategies.